BAHASA DAERAH DOMINAN DI KABUPATEN MALINAU - Arifin, M. Bahri; Mursalim, Mursalim; Rijal, Syamsul (Fakultas Ilmu Budaya, Universitas Mulawarman, 2016)
This article describes the dominant local languages with the highest number of usage areas in Malinau Regency of North Kalimantan Province. The data in this article is based on and become part of the Research Repot on The Profile of Local Languages in Malinau Regency (Arifin, et.al, 2015). The research was designed in qualitatif approach and descriptive methode toward the local languages used in the daily communication of the people in the regency. Data colleting was done with interview and recording techniques. Data analysis was carried out with tracing technique. The decision of weather or not a status of a local language belong to dominant one is based on the intensity of usage variabel. The criteria applied was that when a language is used in the daily communication by the largest number of population of a particular area (desa), the status of that language belongs a dominant one in that particular area (desa). Meanwhile a language with a minor number of speakers was labeled as the complementary language. Data analysis indicated that there are a total of 21 dominant local languages and another 7 complementary languages in Malinau Regency. Three out of the total 21 dominant local languages with the highest number of usage areas are respectively as fallows: Punan Language 30 out of a total of 106 areas/desas (28.30%), Lundayeh Language 24 areas/desas (22.64%), and Lepuk Tau Language 8 areas/desas (7.54%). Keywords: local language in Malinau, language variety, dominat language, complementary language